Incidental finding of "ghost" on echocardiography after transvenous lead extraction among systemic infection patients. (14th October 2021) - Azari, A; Kristjansdottir, I; Gadler, F
Abstract: Background: Ghosts are described as cylindrical and oscillating structures diagnosed after transvenous lead extraction (TLE) and may consist of thrombi, vegetations and fibrous sheaths. Presence of ghosts is found to be associated with poor outcomes. Purpose: The aim of this study was to estimate the proportion of patients with ghosts and to describe the characteristic features of `'ghosts" seen post-TLE in a retrospective series of systemic infection patients. Methods: Medical journals including echocardiography studies of systemic infection patients undergoing TLE between January 1, 2010 and December 31, 2018 were analysed. Results: A total of 258 patients (72% males, mean age 71±12 years), underwent TLE due to systemic infection. Staphylococcus aureus was the dominant microorganism isolated in blood cultures (40%). Echocardiography identified ghosts as incidental findings in 15 (6%) patients, 1–23 day(s) (median, 5; mean, 7±6 days) post-TLE and ghosts remained up to 51 days post-TLE. Ghosts were described as tubular, echodense and mobile tissues with variety of dimensions (2–50 mm) on echocardiography, mostly localised in right atrium (40%). Ghosts were visually described by surgeons as vegetations on tricuspid valve, organised thrombotic material in superior/inferior vena cavae and more loose thrombotic materials in right atrium in 2 patients who underwent open heart surgery after TLE. Echocardiography could not certainly differentiate between non-infectious tissue and infectious vegetations, thereby endocarditis treatment was prolonged to at least 12 days (mean, 29±14 days) post-TLE in the ghost group. Conclusion: Although this was a retrospective analysis and ghosts were incidental findings rather than differential diagnosis, which may have underestimated the proportion ghosts identified, ghosts were relatively common in this cohort. Presence of ghosts caused management challenges for clinicians. There is a great need for large multicentre studies enabling establishment of guidelines for diagnosis and management of this common post-TLE finding. Funding Acknowledgement: Type of funding sources: None.